High-performance sono/nano-catalytic system: CTSN/Fe3O4–Cu nanocomposite, a promising heterogeneous catalyst for the synthesis of N-arylimidazoles. Issue 69 (5th December 2019) - Taheri-Ledari, Reza; Hashemi, Seyed Masoud; Maleki, Ali
Abstract : High-performance sono/nano-catalytic system: CTSN/Fe3 O4 –Cu nanocomposite, a promising heterogeneous catalyst for the synthesis of N -arylimidazoles with high yields. Abstract : Herein, a promising heterogeneous nanoscale catalytic system constructed of chitosan (CTSN, as a polymeric basis), iron oxide nanoparticles (Fe3 O4 NPs, as the magnetic agent), and copper oxide nanoparticles (CuO NPs, as the main catalytic active site) is presented. Firstly, a convenient synthetic route for preparation of this novel nanocatalyst (CTSN/Fe3 O4 –Cu) is presented. Further, the synergistic catalytic effect between the novel-designed catalyst and ultrasound waves (USW) in N -arylation coupling reactions of the imidazole derivatives (using various aryl halides) is precisely discussed. Concisely, high reaction yields (98%) have been obtained in short reaction time (10 min) through applying a partial amount (0.01 g) of this nanocatalyst. As the main reason for high catalytic activity of CTSN/Fe3 O4 –Cu, nanosized cluster-shaped morphology, which provides a wide surface active area, can be expressed. However, as the most distinguished properties of CTSN/Fe3 O4 –Cu catalytic system, high convenience in separation and excellent reusability could be mentioned. CTSN/Fe3 O4 –Cu nanocomposite can be easily recovered by using an external magnet and reused at least for eight times with no significant decline in the catalytic activity. Structural characterizations of this novel system have been done by various analytical methods and the obtained results have been well interpreted in the context.